Generational Investment Behavior: The Influence of Risk Tolerance and Technology Adoption in an Evolving Financial Landscape - Rob Kim Marjerison; Hang Dong; Jong Min Kim (SAGE Open)
This study explores generational differences in investment behavior, focusing on the moderating roles of risk tolerance and technology adoption in shaping financial decisions across asset types. Generation Z, having entered adulthood during the COVID-19 pandemic, exhibits a more risk-averse approach compared to Generation Y and Generation X, favoring safer, liquid assets amidst economic uncertainty. The study confirms that as Gen Z’s risk tolerance increases, their preference shifts towards moderate-risk investments like gold, though high-risk assets remain largely unattractive. In contrast, technology adoption plays a more significant role for Millennials (Gen Y), enhancing their engagement with both safe and moderate-risk investments, while having minimal impact on Gen Z’s behavior. These findings provide valuable insights for financial policymakers and institutions, emphasizing the need for targeted strategies that align with the unique preferences of each generation. Tailoring financial policies and investment products to generational needs can foster sustainable economic development by encouraging engagement across diverse market segments.